SARS CoV-2 Nucleoprotein Enhances the Infectivity of Lentiviral Spike Particles - Mishra, Tarun; Sreepadmanabh, M.; Ramdas, Pavitra; Sahu, Amit Kumar; Kumar, Atul; Chande, Ajit (Frontiers in Cellular and Infection Microbiology, 2021)
The establishment of SARS CoV-2 spike-pseudotyped lentiviral (LV) systems has enabled the rapid identification of entry inhibitors and neutralizing agents, alongside allowing for the study of this emerging pathogen in BSL-2 level facilities. While such frameworks recapitulate the cellular entry process in ACE2+ cells, they are largely unable to factor in supplemental contributions by other SARS CoV-2 genes. To address this, we performed an unbiased ORF screen and identified the nucleoprotein (N) as a potent enhancer of spike-pseudotyped LV particle infectivity. We further demonstrate that the spike protein is better enriched in virions when the particles are produced in the presence of N protein. This enrichment of spike renders LV particles more infectious as well as less vulnerable to the neutralizing effects of a human IgG-Fc fused ACE2 microbody. Importantly, this improvement in infectivity is observed with both wild-type spike protein as well as the D614G mutant. Our results hold important implications for the design and interpretation of similar LV pseudotyping-based studies.